If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(5) + -7 = 53 Reorder the terms for easier multiplication: 5x + -7 = 53 Reorder the terms: -7 + 5x = 53 Solving -7 + 5x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 5x = 53 + 7 Combine like terms: -7 + 7 = 0 0 + 5x = 53 + 7 5x = 53 + 7 Combine like terms: 53 + 7 = 60 5x = 60 Divide each side by '5'. x = 12 Simplifying x = 12
| 15+0.75a=13+0.50a | | y=-4+2x | | -3b+9=9-3b | | K=412k-3 | | -16-(-8)= | | 7x-3y=73 | | -4=x-3 | | x-y=-15 | | x(8)+17=33 | | 2+10x=65+x | | r+6-5r=14-2r | | 20+1.50a=14+2a | | 2a-2+7= | | x-17=-27 | | 5c^2*2c^2= | | g-9=-21 | | 4(3y-x)=5z-18 | | 3x-6x=-24 | | 4x^3=-108 | | -4-12= | | -13+b=31 | | 2x+4y=-18 | | =b^3-3b^2+4b+8 | | y=b^3-3b^2+4b+8 | | b^3-3b^2+4b+8=0 | | -3=d+(-4) | | b^3-3b^2+4b+8=t | | t=5m+5w | | 4(-10-5x)=40 | | r-(-7)=-16 | | x-(-8)=13 | | t-(-4)=4 |